Critical Care in Cardiac Surgery Patients with COVID-19: International and Own Experience - Koltunova, G. B.; Avramenko, L. M.; Voityuk, V. V.; Chyzh, K. P. (Ukrainian Journal of Cardiovascular Surgery, 2021)
The widespread occurrence of coronavirus disease 2019 (COVID-19) in the world has led to a sharp de-crease in the number of cardiac surgery interventions and had a negative impact on treatment outcomes. We present an overview of the available literature on the effects of COVID-19 on cardiac surgery at this time. The lack of randomized studies and guidelines on the tactics of perioperative management of patients with cardiovascular pathology encourages to rely on isolated clinical cases presented in the literature. The presence of cardiovascular disease in COVID-19 patients has been identified as a risk factor associated with high morbidity and mortality from the first days of the pandemic. In addition to older age, chronic comorbidities increase the risk of severe COVID-19 infection as well as its lethal outcome. Among the predictors of 30-day mortality in COVID-19 patients in the postoperative period the following were under-lined: male sex (p˂0.001), high risk class according to the American Society of Anesthesiologists (ASA) (p˂0.001), age over 70 years (p˂0.001), emergency surgery (p = 0.026), oncological surgery (p = 0.046). To date, there are no studies on the perioperative management of cardiac surgery patients with acquired heart disease with persistent post-COVID-19 lung disease. We present the results of our own experience of perioperative management of a cardiac surgery patient with COVID-associated outpatient bilateral polysegmental pneumonia. Patients with cardiac surgery after COVID-19 required intensive preoperative preparation. Appointment of the proposed scheme of antibacterial therapy in combination with corticosteroids has reduced the intensity of inflammatory changes in lung tissue. Surgical improvement of intracardiac hemodynamics under cardiopulmonary bypass led to complete reduction of lung parenchyma injury and restoration of the respiratory system. Results. In patients with acquired heart disease, respiratory failure can be caused not only by post-COVID-19 lung injury, but also by impaired intracardiac hemodynamics with increased pulmonary artery pressure due to the initial heart disorders. Restoration of adequate gas exchange function in the group of post-COVID-19 patients is ineffective without timely cardiac surgery.